2018
DOI: 10.1136/bmjopen-2017-018794
|View full text |Cite|
|
Sign up to set email alerts
|

Randomised controlled trial to determine the efficacy and safety of prescribed water intake to prevent kidney failure due to autosomal dominant polycystic kidney disease (PREVENT-ADPKD)

Abstract: IntroductionMaintaining fluid intake sufficient to reduce arginine vasopressin (AVP) secretion has been hypothesised to slow kidney cyst growth in autosomal dominant polycystic kidney disease (ADPKD). However, evidence to support this as a clinical practice recommendation is of poor quality. The aim of the present study is to determine the long-term efficacy and safety of prescribed water intake to prevent the progression of height-adjusted total kidney volume (ht-TKV) in patients with chronic kidney disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“… # Odds ratio reported only for male participants retained [ 39 ] or division of age groups [ 59 ] * Data not divided between those identifying as men and those who identify as women a Study protocol of PREVENT ADPKD [ 63 ], substudy visits not specified [ 38 ] but is assumed 2 (questionnaire, interview) in a 16 month period b [ 40 ] and study protocol [ 60 ]. Study launched reported on study website [ 64 ] c Protocol paper describes 3 Stages after recruiting a population-based cohort [ 60 ], not described in [ 40 ] d Study contact were text messages the amount, timing and frequency of SMS text messages were decided by participant [ 44 ] e Completers of final postal survey f Last wave (wave 5) of the study (77 – 87 years old) completers of follow-up, no male specific data given for wave 1–4 [ 45 ] g Protocol paper describes the use of census data at 1996, 2001 and 2006 [ 65 ] h Yearly visits with an option to fill in a complementary questionnaire each month [ 43 ] i Two studies were included WebMOVE and MOVE-SMI [ 53 ] j Sub-study was randomly selected from WebMOVE and MOVE-SMI groups and not stratified by sex [ 53 ] k Details only recruitment strategies [ 54 ] l Due to its longitudinal nature, it is assumed this study has more than 3 visits in the 12-year reported period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… # Odds ratio reported only for male participants retained [ 39 ] or division of age groups [ 59 ] * Data not divided between those identifying as men and those who identify as women a Study protocol of PREVENT ADPKD [ 63 ], substudy visits not specified [ 38 ] but is assumed 2 (questionnaire, interview) in a 16 month period b [ 40 ] and study protocol [ 60 ]. Study launched reported on study website [ 64 ] c Protocol paper describes 3 Stages after recruiting a population-based cohort [ 60 ], not described in [ 40 ] d Study contact were text messages the amount, timing and frequency of SMS text messages were decided by participant [ 44 ] e Completers of final postal survey f Last wave (wave 5) of the study (77 – 87 years old) completers of follow-up, no male specific data given for wave 1–4 [ 45 ] g Protocol paper describes the use of census data at 1996, 2001 and 2006 [ 65 ] h Yearly visits with an option to fill in a complementary questionnaire each month [ 43 ] i Two studies were included WebMOVE and MOVE-SMI [ 53 ] j Sub-study was randomly selected from WebMOVE and MOVE-SMI groups and not stratified by sex [ 53 ] k Details only recruitment strategies [ 54 ] l Due to its longitudinal nature, it is assumed this study has more than 3 visits in the 12-year reported period.…”
Section: Resultsmentioning
confidence: 99%
“…a Study protocol of PREVENT ADPKD [ 63 ], substudy visits not specified [ 38 ] but is assumed 2 (questionnaire, interview) in a 16 month period…”
Section: Resultsmentioning
confidence: 99%
“…A smaller study including 32 participants looks at change in total kidney volume after 1 year (NCT03102632) and a larger study, consisting of 180 ADPKD patients who will be randomized to control (usual fluid intake) or intervention (individualized daily fluid intake to reduce osmolality to ≤270 mOsmol/kg) during 36 months. End points will be change in total kidney volume and estimated GFR [69]. Until results of these studies become available, the question is what to advise to ADPKD patients.…”
Section: Water and Osmolar Intakementioning
confidence: 99%
“…Since increased fluid intake results in suppression of vasopressin this approach is patho-physiologically quite similar to tolvaptan therapy (vasopressin receptor blockade). A recently launched prospective trial aims at exactly this similarity [9]: in a randomized multi-centre trial 180 ADPKD patients with a residual GFR ≥ 30 mL/min/1.73 m 2 will be treated with either standard therapy and uncontrolled fluid intake or standard therapy and an individualized, prescribed and controlled fluid intake strictly lowering the urine osmolality below 270 mOsmol/kg.…”
Section: Life Stylementioning
confidence: 99%